Jogos no ensino-aprendizagem de multiplicação no 6º ano - LIMA, Cledson Silva (2024)
The purpose of this work was to investigate the influence of the game in the teaching learning of Mathematics and to analyze which effects the games can provide to the teaching-learning process of multiplication in the 6th grade. The research carried out is of a qualitative type, subdivided into two moments: a survey of the literature and application of a survey test and, subsequently, pedagogical intervention through application. A script of structured interviews was planned with the mathematics teacher of the 6th year of Elementary School II, and at the end of each experience with games in the classroom involving the mathematics content, probe tests were carried out among the students of the class. During the research, it was observed how important it is to use games in Mathematics classes, making a more creative and participatory class for the student. It was also found that although the school provides games and manipulative materials in its collection, this methodology is rarely used by teachers and, when used, has little relationship with the learning objectives.